Dynamic Modelling of Heat Transfer - Palmqvist, Olle (My University, 2012)
Flexible power plant control has considerable economical benefit for power plant owners in the liberalised and highly dynamic electricity market found in many countries. While offering a high degree of operational flexibility, sophisticated and highly automated power plant control schemes leads to less active interference on operation by power plant operators. Full-scope dynamic simulators offers an alternative environment where operators and engineers can develop crucial knowledge about plant dynamics. The focus in the present work is to develop a dynamic model of a supercritical steam power plant boiler that could serve as a representation of the boiler in a power plant simulator. The boiler model is separated into subcomponents; a water wall, two superheaters and an economizer. Each compo- nent consists of one discrete volume of flue gas respectively water that are able to exchange heat by radiation or convection. The dynamic 1-dimensional heat and mass balance equations are based on an ideally-stirred tank approximation. A fictional boiler were dimensioned, and simulations were carried out according to the sliding pressure operation principle where steam mass flow and pressure is varied directly proportional to the load. The simulation results indicate that water flow dynamic phenomena strongly govern the dynamic water temperature response during load changes.
Keywords: Övrig annan teknik; Energi; Hållbar utveckling; Other Engineering and Technologies not elsewhere specified; Energy; Sustainable Development